2018
DOI: 10.1097/md.0000000000010102
|View full text |Cite
|
Sign up to set email alerts
|

The altered Granger causality connection among pain-related brain networks in migraine

Abstract: Numerous fMRI studies have confirmed functional abnormalities in resting-state brain networks in migraine patients. However, few studies focusing on causal relationships of pain-related brain networks in migraine have been conducted. This study aims to explore the difference of Granger causality connection among pain-related brain networks in migraine without aura (MWoA) patients.Twenty two MWoA patients and 17 matched healthy subjects were recruited to undergo resting-state fMRI scanning. Independent componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Specifically, activity was spread over a larger extent over fronto-central and occipital regions in MA [ 175 ], and information was estimated to be flowing posterior to anterior [ 176 ]. Granger causality increased with laser stimulation (to cause pain) in those with migraine [ 177 ], and Granger causality was increased in migraine in specific areas associated with pain processing [ 178 ]. Overall, there is evidence to suggest that information spreads more readily in migraine from posterior to anterior regions, specifically in alpha and beta bands.…”
Section: Linking Models To Neural Activity During Aura (And Headache)mentioning
confidence: 99%
“…Specifically, activity was spread over a larger extent over fronto-central and occipital regions in MA [ 175 ], and information was estimated to be flowing posterior to anterior [ 176 ]. Granger causality increased with laser stimulation (to cause pain) in those with migraine [ 177 ], and Granger causality was increased in migraine in specific areas associated with pain processing [ 178 ]. Overall, there is evidence to suggest that information spreads more readily in migraine from posterior to anterior regions, specifically in alpha and beta bands.…”
Section: Linking Models To Neural Activity During Aura (And Headache)mentioning
confidence: 99%
“…These studies are model-driven methods that require considerable prior knowledge. In this study, we used Granger causality analysis (GCA), which is a data-driven EC calculation method and can be directly applied to the resting-state data ( Liu et al, 2018 ; Ning et al, 2018 ; Shi et al, 2019 ). It has been widely used for time-directed prediction between BOLD fMRI time series to measure the causal effects among brain regions ( Jiao et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that decreased rs-FCS of the left IFG in PDM patients had increased (normalized) after moxibustion. Previous neuroimaging studies have suggested that IFG was related to chronic pain ( Ning et al, 2018 ). The left IFG, which is reportedly involved in executive cognitive function and episodic memory, belongs to the executive control network (ECN) ( Xue et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%